Alex Tessa Duder.. - Duder, Tessa. (Oxford University Press, 1987)
Fifteen-year-old Alex struggles to overcome personal trauma and hardship as she competes with her arch rival for a place on the New Zealand swimming team participating in the 1960 Olympic Games in Rome.